치과 의료기관의 방사선 안전관리 지침서 개발의 필요성 - 황소라; So Ra Hwang (대한구강보건학회지, 2019)
Objectives: The objectives of this study were to determine the radiation safety status of dental care institutions and to contribute to the development of guidelines for radiation protection in dental clinics in order to improve the work environment and reduce the radiation hazard for practitioners. Methods: The subjects were selected using a convenience sampling. A total of 300 subjects participated in this study, including 150 dental hygienists from dental clinics in Gwangju Metropolitan City with radiation-related work experience and 150 dental hygienists who had participated in a seminar hosted by the Korean Dental Insurance Manager Association held on January 17, 2016. For the survey, self-entry questionnaires were used, and the collected data were analyzed by performing a frequency analysis using cross tabulation (c2-test) and t-test, one-way analysis of variance, and multiple regression analysis. Results: The awareness on radiation protection among dental hygienists showed 4.4 out of 5 points, which was high, but the practice of radiation protection was overall poor. For the necessity of developing radiation protection guidelines, 91.9% answered “Yes, it is necessary.”. Conclusions: The level of radiation protection practiced at dental healthcare centers was much lower than the awareness of it and showed that the requirement of guidelines for radiation protection was high. Therefore, institutional devices require the development and utilization of various types of radiation protection guidelines in order to mitigate radiation risks and improve the work environment.